Remission and relapse in a drug-resistant epilepsy population followed prospectively - Callaghan, Brian (2011)
PURPOSE: We investigated the cumulative probability of seizure remission and relapse in an adult population with drug-resistant epilepsy and frequent seizures. In addition, we determined clinical predictors of remission and relapse in this population. METHODS: In 2003, we identified 246 patients at a single center with drug-resistant epilepsy defined as at least one seizure per month and failure of at least two antiepileptic drugs. These patients were followed prospectively (cohort design). We examined the cumulative probability of seizure remission and relapse in this population using Kaplan- Meier methodology. Clinical predictors of remission and relapse were also evaluated using Cox regression analysis. KEY FINDINGS: The estimated cumulative probability of 12-month seizure remission was 34.6% at 7 years in the entire population and 33.4% when limited to those without surgery. The risk for relapse after a 12-month period of seizure remission was 71.2% at 5 years. Negative predictors of seizure remission included developmental delay, symptomatic generalized epilepsy syndrome, duration of intractability, and number of antiepileptic drugs failed. Localization-related epilepsy was the only negative predictor of relapse. SIGNIFICANCE: Among patients with drug-resistant epilepsy, 5% per year enter seizure remission even with a follow-up of 6 years. However, a substantial proportion of these patients relapse after the first year following a remission. The large proportion of patients entering a significant remission gives these patients hope; however, caution should be advised when discussing the likelihood of future seizures.